Mediating Role of Learning Skills in the Relationship between Student Achievements in Basic Science and Teaching Skills in the Twenty-First Century in Government-aided Secondary Schools - Lucy Aja; Okechukwu Sunday Abonyi; Balafama Green; Tukur Muhammad; Iruka John Elom; Mohammad Lubega; Aquila Modupe Otitoju (Scientia Publica Media, 2025)
This study investigated the mediating role of learning skills in the relationship between student achievements in basic science and teaching skills in government-aided secondary schools in Ebonyi State, Nigeria. The study utilized a cross-sectional correlation research design. The target population encompasses 17 secondary schools of 9,062 students from the 2023/2024 academic session. A sample size of 340 students was selected using a stratified random sampling technique through Cochran’s formula. A self-structured questionnaire was developed and rigorously evaluated for coherence, relevance, and clarity, with revisions from science education experts incorporated into the final version. A pilot study involving 45 participants outside the main sample area confirmed the validity and reliability of the instrument, achieving a Cronbach’s alpha coefficient of 0.775, surpassing the acceptable threshold of 0.70. The data collected were analyzed using SPSS version 27 and descriptive statistics to address key research questions related to student achievement levels, perceived teaching skills, and learning skills. The findings indicated that students demonstrate a robust understanding of basic science concepts, indicating effective teaching methods. However, a gap existed between students’ theoretical knowledge and their confidence in problem-solving, highlighting the need for enhanced problem-based learning strategies. The study also revealed that while students showed high motivation for assignments, traditional assessments may not fully capture their comprehension. Furthermore, there are limited opportunities for collaborative projects and technology integration, and challenges remain in fostering higher-order thinking skills. The study also showed that students expressed the importance of constructive feedback and hands-on learning, but required additional support for self-reflection and active participation. Finally, improving teacher-student relationships and creating a more inclusive learning environment are essential for enhancing educational outcomes. From the results’ findings, the researchers recommended that the PBL strategy, technology, and collaboration should be integrated into students’ learning.